(untitled) (Annals of Medical Research, 2023)
Aim: Determination of the axon numbers of nerve fibers and evaluation of the parenchyma/stroma ratios to indicate the density of the periaxonal tissue (myelin sheath and periaxonal connective tissue) were aimed by using stereological methods on the histological sections obtained from the sciatic and tibial nerves of the human fetuses. Materials and Methods: This histomorphometric study was carried out on 20 aborted human fetuses (14 males, 6 females, between 12 and 38 gestational weeks) with no external anomalies or malformation. Peripheral nervous tissue specimens harvested from the three levels [proximal (sciatic nerve), middle (first part of the tibial nerve), and distal (distal part of the tibial nerve) levels] through the lower extremities, by anatomical dissection, on either side. Histological sections were prepared. Digital images of the sections were used for the stereological study. Results: The results showed (I) the axon number of peripheral nerves increases as the fetal period progresses; (II) the axon number of peripheral nerves do not change from proximal to the distal specimen levels; (III) the axon number of peripheral nerves increases at the same rate throughout the nerve; (IV) the parenchyma/stroma ratio of peripheral nerves does not change along with the nerve, during the fetal period; (V) the parenchyma/stroma ratio of the peripheral nerves does not vary between specimen levels. Conclusion: Our results may contribute to the experimental and clinical research primarily related to sciatic and tibial nerves and the histological interpretation of fetal autopsy materials in fields such as fetopathology and forensic medicine.